A Preliminary Gene Map for the Van der Woude Syndrome Critical Region Derived from 900 kb of Genomic Sequence at 1q32–q41 - Schutte, Brian C.; Bjork, Bryan C.; Coppage, Kevin B.; Malik, Margaret I.; Gregory, Simon G.; Scott, Deborah J.; Brentzell, Luci M.; Watanabe, Yoriko; Dixon, Michael J.; Murray, Jeffrey C. (Genome Research, 2000)
Van der Woude syndrome (VWS) is a common form of syndromic cleft lip and palate and accounts for ∼2% of all cleft lip and palate cases. Distinguishing characteristics include cleft lip with or without cleft palate, isolated cleft palate, bilateral lip pits, hypodontia, normal intelligence, and an autosomal-dominant mode of transmission with a high degree of penetrance. Previously, the VWS locus was mapped to a 1.6-cM region in 1q32–q41 between D1S491 and D1S205, and a 4.4-Mb contig of YAC clones of this region was constructed. In the current investigation, gene-based and anonymous STSs were developed from the existing physical map and were then used to construct a contig of sequence-ready bacterial clones across the entire VWS critical region. All STSs and BAC clones were shared with the Sanger Centre, which developed a contig of PAC clones over the same region. A subset of 11 clones from both contigs was selected for high-throughput sequence analysis across the ∼1.1-Mb region; all but two of these clones have been sequenced completely. Over 900 kb of genomic sequence, including the 350-kb VWS critical region, were analyzed and revealed novel polymorphisms, including an 8-kb deletion/insertion, and revealed 4 known genes, 11 novel genes, 9 putative genes, and 3 psuedogenes. The positional candidates LAMB3, G0S2, HIRF6, and HSD11 were excluded as the VWS gene by mutation analysis. A preliminary gene map for the VWS critical region is as follows: CEN-VWS33-VWS34-D1S491-VWS1-VWS19-LAMB3G0S2-VWS26-VWS25-HSD11-ADORA2BP-VWS17-VWS14-HIRF6-VWS2-VWS18-D1S205-VWS23-VWS20-VWS30-VWS31-VWS35-VWS37VWS38-HIPP-RNASEH1P-VWS40-VWS42-VWS41-TEL. The data provided here will help lead to the identification of the VWS gene, and this study provides a model for how laboratories that have a regional interest in the human genome can contribute to the sequencing efforts of the entire human genome.